OP0059 Golimumab versus tocilizumab for severe and refractory juvenile idiopathic arthritis-uveitis. multicenter study of 33 patients. (15th June 2017) - Casas, L Domínguez; Calvo-Río, V; Calvo, I; González-Fernández, M; Lόpez-Montesinos, B; Mesquida, M; Adán, A; Hernández, M; Maíz, O; Blanco, A; Atanes, A; Bravo, B; et al.
Abstract : Background: Uveitis is a severe manifestation of Juvenil Idiopathic Arthritis (JIA). Anti-TNFa are recommended in refractory cases, mainly infliximab (IFX) or adalimumab (ADA) (Levy-Clarke et al. Ophthalmology 2014; 121: 785–796). However, sometimes they are ineffective, contraindicated or not tolerated. The next therapeutic step is not defined. Objectives: To compare the efficacy of Golimumab (GLM) and Tocilizumab (TCZ) in related AIJ uveitis refractory to conventional immunosuppressive drugs and anti-TNFα. Methods: Multicenter study of 33 patients with uveitis associated-JIA. They were refractory to conventional treatment with high dose of corticosteroids and at least a) one conventional immunosuppressive drug and b) one anti-TNFa. For this reason it was decided to iniciate TCZ or GLM. TCZ was used in 25 patients: 8 mg/kg/4 w iv (n=21), 8 mg/kg/2 w (n=2); 8 mg/kg/8 w (n=1) and 2.9 mg/kg sc/w (n=1). GLM was used in 8 patients (50 mg/sc/month). We assessed visual acuity (VA), degree of intraocular inflammation, vitreous inflammation and macular thickening (with OCT). Quantitative variables were expressed with mean±SD or median [IQR], according to its distribution. They were compared with the Student t or the Mann-Whitney U test, respectively. Dichotomous variables were expressed as percentages and compared by the chi-square test. Results: We studied 33 patients/61 affected eyes. There were no significant differences between TCZ and GLM at baseline in sex (♂/♀;4/21 vs 3/5; p=0.19), mean age (18.5±8.3 vs 19.9±8.7; p=0.55), positive ANA (95% vs 100%; p=0.7), uveitis duration before TCZ or GLM onset (116.4±93.6 vs 142.3±74.7 p=0.46), number of previous biological treatments (1.9±1.1 vs 2±1.4; p=0.84), VA (0.57±0.35 vs 0.5±0.37; p=0.42), combined immunosuppressive therapy (88% vs 75%; p=0.37), presence of cells in the anterior chamber (median, 1 [0–1] vs 1 [0.25–1.5]; p=0.6), vitritis (0 [0–0] vs 0 [0–1]; p=0.7), macular thickening (358.7±92.2 vs 313.6±77.1; p=0.32). There were no significant difference in the efficacy between TCZ and GLM (TABLE). After a mean follow-up of 20.48±11.7 months with TCZ and 24.25±17 months with GLM the following side effects were observed: TCZ: viral conjunctivitis plus bullous impetigo (n=1), severe thrombocytopenia and pneumonia. This last patient showed hemolytic anemia, thrombocytopenia and splenomegaly, for this reason treatment with TCZ was discontinued. With GLM cutaneous reaction was observed in 2 patients. Conclusions: TCZ and GLM seem to be equally effective and safe for refractory uveitis associated-JIA. The superiority of one or the other should be established with prospective randomized studies "Head to Head" Disclosure of Interest: None declared